Preparing for genocide: Community work in Rwanda - Evelina Bonnier; Jonas Poulsen; Thorsten Rogall; Miri Stryjan (Uppsala University, Department of Economics, 2015)
How do political elites prepare the civilian population for participation in violent conflict? We empirically investigate this question using village-level data from the Rwandan Genocide in 1994. Every Saturday before 1994, Rwandan villagers had to meet to work on community infrastructure, a practice called Umuganda. This practice was highly politicized and, in the years before the genocide, regularly used for spreading political propaganda. To establish causality, we exploit cross-sectional variation in meeting intensity induced by exogenous weather fluctuations. We find that an additional rainy Saturday resulted in a five percent lower civilian participation rate in genocide violence. These results pass a number of indirect tests of the exclusion restriction as well as other robustness checks and placebo tests.
urn:nbn:se:uu:diva-242293
Keywords: D74; N47; 330; Conflict; Rainfall